ANALISIS SENSITIVITAS ETIS MAHASISWA UNIVERSITAS ISLAM ’45 BEKASI - Nurma Risa (JRAK: Journal of Accounting Research and Computerized Accounting, 2011)
This study purposes to examine wether there is difference of sensitivity ethic between UNISMA Bekasi students on individual factors (program, gender). The populations of this research are students in Universitas Islam ’45 Bekasi (UNISMA Bekasi) especially Economic Faculty students. The analysis of this research using independent sample t-test dan Mann whithney u-test as a confirmation. The result of hypothesis test shows there is no significantly sensitivity ethic differences between accounting student and management student. And there is also no significantly sensitivity ethic differences between male andfemale student.